DISAPPEARANCE OF WITNESSES’ OWN WORDS - OKAWARA, Mami Hirake (Comparative Legilinguistics, 2012)
This paper discusses the characteristics of prosecutor’s language that would appear in the prosecution witness’s answers during direct examination. I performed a linguistic comparison of the language that is used in a witness’s answers against that of five relevant documents, which include a prosecutor’s opening statement, a prosecutor’s final statement, 11 samples of suspect’s statements from the handbook for investigating officers and one from witness’s personal letters. I would like to argue that as the witness’s answer had the features of a prosecutor’s language as well as written language, the prosecutor’s ten meetings with the witness immediately before the trial may have possibly influenced not only the witness’s language but also the content of the testimony itself. The analysis of this paper is based upon my expert witness opinion that was submitted to the Tokyo High Court and Japanese Supreme Court for the case in question.